2023
DOI: 10.3389/fmicb.2023.1131599
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Ganoderma lingzhi (Agaricomycetes) response to Trichoderma hengshanicum infection

Abstract: Green mold caused by Trichoderma spp. has become one of the most serious diseases which threatening the production of Ganoderma lingzhi. To understand the possible resistance mechanism of the G. lingzhi response to T. hengshanicum infection, we examined the G. lingzhi transcript accumulation at 0, 12, and 24 h after T. hengshanicum inoculation. The gene expression analysis was conducted on the interaction between G. lingzhi and T. hengshanicum using RNA-seq and digital gene expression (DGE) profiling methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…A recent study showed that 19 classes of PR proteins can be distinguished based on structural similarity and functional activity [ 1 , 4 ], of which, thaumatin-like proteins (TLPs)—the homologies of sweet-tasting thaumatin isolated from the plant Thaumatococcus daniellii —belong to the PR-5 family [ 5 , 6 ]. Growing evidence shows that TLPs are involved in resistance to a variety of fungal diseases in many species, such as Gossypium hirsutum [ 7 ], Gossypium barbadense [ 8 ], Solanum lycopersicum [ 4 , 9 ], Phyllostachys edulis [ 10 ], Ganoderma lingzhi [ 11 ], Triticum aestivum L. [ 12 , 13 ], Carya cathayensis [ 14 ], Fragaria ananassa [ 15 ], Allium sativum L. [ 16 ], Pinus radiata [ 17 ], Lentinula edodes [ 18 ], Camellia sinensis [ 19 ], Cucumis melo L. [ 20 ], Avena nuda [ 5 ], Musa acuminate [ 21 ], Manihot esculenta [ 22 ], Vitis amurensis [ 23 ], Populus szechuanica [ 24 ], Camellia sinensis [ 25 ], Piper colubrinum [ 26 ], Cynanchum komarovii [ 27 ], Castanea sativa [ 28 ], Actinidia chinensis [ 29 ], and Lyophyllum shimeji [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that 19 classes of PR proteins can be distinguished based on structural similarity and functional activity [ 1 , 4 ], of which, thaumatin-like proteins (TLPs)—the homologies of sweet-tasting thaumatin isolated from the plant Thaumatococcus daniellii —belong to the PR-5 family [ 5 , 6 ]. Growing evidence shows that TLPs are involved in resistance to a variety of fungal diseases in many species, such as Gossypium hirsutum [ 7 ], Gossypium barbadense [ 8 ], Solanum lycopersicum [ 4 , 9 ], Phyllostachys edulis [ 10 ], Ganoderma lingzhi [ 11 ], Triticum aestivum L. [ 12 , 13 ], Carya cathayensis [ 14 ], Fragaria ananassa [ 15 ], Allium sativum L. [ 16 ], Pinus radiata [ 17 ], Lentinula edodes [ 18 ], Camellia sinensis [ 19 ], Cucumis melo L. [ 20 ], Avena nuda [ 5 ], Musa acuminate [ 21 ], Manihot esculenta [ 22 ], Vitis amurensis [ 23 ], Populus szechuanica [ 24 ], Camellia sinensis [ 25 ], Piper colubrinum [ 26 ], Cynanchum komarovii [ 27 ], Castanea sativa [ 28 ], Actinidia chinensis [ 29 ], and Lyophyllum shimeji [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma employs colonization strategies to establish itself within the host, overcoming plant defense mechanisms [ 20 , 21 ]. The pathogen also triggers a series of defense responses in the plant, and understanding these interactions can help develop strategies to enhance plant resistance and suppress Ganoderma proliferation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%